ChemInform Abstract: Phospho Sulfonic Acid: An Efficient and Recyclable Solid Acid Catalyst for the Solvent‐Free Synthesis of α‐Hydroxyphosphonates and Their Anticancer Properties. Issue 36 (September 2015) - Kalla, Reddi Mohan Naidu; Lee, Hye Ri; Cao, Jiafu; Yoo, Jin‐Wook; Kim, Il
Abstract A small library of biologically active α‐hydroxyphosphonates is prepared by Pudovik reaction of salicylaldehydes with dialkyl phosphites in the presence of a solid acid catalyst.